Superlative QP “Hyper-Raising” in dialectal Spanish: the role of dormant Edge Features - Sáez del Álamo, Luis Ángel (Borealis – An International Journal of Hispanic Linguistics, 2020)
In this paper I deal with a particular relative-clause superlative construction attested in Spanish dialects like Canariense (Bosque & Brucart 1991) and Puerto Rican (Rohena-Madrazo 2007), among others. In this construction the superlative quantifier raises to the left of the complementizer of the relative clause. However, as observed by Bosque & Brucart (1991), only object quantifiers can move in this way; subject quantifiers cannot. I account for this assymmetry by assuming Bianchi’s (2000) raising analysis for relative clauses, Kandybowicz’s (2009) theory on edge features and Pesetsky & Torrego’s (2001) proposal on Tense-to-Comp movement (among other assumptions). Object-quantifier movement correlates with Tense-to- Comp movement, which activates an edge feature for objects and allows them to escape the phasal minimal domain undergoing Transfer. This is not possible for subject-quantifier movement. I also propose that the determiner introducing a relative clause bears an uninterpretable [Superlative] feature with clitic-like properties. This feature forces the determiner to post-syntactically cliticize to the superlative quantifier degree word, a process which requires linear adjacency. This accounts for certain restrictions on this sort of superlative quantifier raising already pointed out by Bosque & Brucart (1991) The proposal (similar to the one in Rohena-Madrazo 2007) that [Superlative] may also be in Force in these dialects (if selected for Force by the determiner) explains a more restrictive (and widespread) variant of this construction.